Traditional Medicines and Globalisation The Future of Ancient Systems of Medicine (Maven Publishers, 2014)
The development of natural products requires the confluence of the modern techniques and integrated approaches in various fields of science and technology. Intention of this book is to highlight different aspects of globalization of traditional medicine with the focus on some crucial and contemporary issues on validation of natural products. Eminent scientists around the globe have contributed for this book on different issues of ethnopharmacology, traditional medicine and globalization. Given the importance on promotion and development of natural products, this book covers various aspects on revitalization of traditional medicines. The contributors have provided an insight into the modem aspects and future of traditional medicine inspired drug development, validation, safety related quality issues, sustainability and globalization. Bringing together expertise from academia and industry, this edited volume provides an overview of traditional medicine with wisdom and know-how in both innovation and commercialization, placing natural product research in a broader sense for readers. This edited volume contains 68 chapters emphasizing several thrust areas of ethnopharmacology and natural products. A wide diversity of chapters has been contributed by eminent personalities throughout the world including Dr. A. P. J. Abdul Kalam, Sri. Shekhar Dutt, Dr. Marco Leonti, Dr. G. A. Cordell, Dr. R. Verpoorte, Dr. P. J. Houghton, Dr. P. Pushpangadan, Dr. Y. K. Gupta, Dr. A.K.S. Rawat, Dr. S.K. Kulkarni, Dr. Colin W. Wright, Dr. S. C. Mandal, Dr. C. K. Katiyar, Dr. T. K. Mukherjee, Dr. S. Rajan, Dr. G. Schemda, Dr. P. K. Debnath, Dr. Bob Alkin, Dr. Elfin Y. Sukandar, Dr. N. Maity, Dr. A. K. Mitra, Dr. E. Hossain, Dr. H. Fukui, Dr. S.Bhadra, Dr. N. Neema, Dr. H. Mizuguchi, Dr. D. Chattopadhyay, Dr. T. Sen, Dr. Erdem Yesilada, Dr. S.K.Mitra, Dr. S.C. Bachar, Dr. S. Karmakar, Dr. G. B. J. Bailly, Dr. P. Haldar, Dr. Y. Oztruk, Dr. S. Pandit, and others. All representing the-state-of-the-art of the field, and thus would be interesting sources for information. This book will be of enormous help to the undergraduate and postgraduate students, researchers and academia and all others working in the area of Ethnopharmacology and natural product research. It will be an imperative addition to the libraries of technical and administrative personnel in the industries and Universities as a potential resource to update their knowledge.
English
Keywords: Medicine; Globalization; traditional medicine